PREDICTING MILK PRODUCTION AND ITS COMPONENTS BY LACTOFERRIN CONCENTRATION IN COLOSTRUM AND MILK OF HOLSTEIN COWS - N. H. Alkudsi; D. A.Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this study was to predict the milk yield and its constituents of first parity-ten Holstein cows through lactoferrin concentration in colostrum and milk. The study was executed at Al-Nasr Dairy Cattle Station, at Essaouira (50 km south of Baghdad) during the period from 15/1/2013 to 1/4/2013. The lactoferrin concentration in colostrum and milk, milk constituents and the minerals concentration were measured. The lactoferrin concentration in colostrum was 732.78+ 28.03mg/L, which was higher than its concentration in milk (541.11+ 19.20 mg/L). Milk constituents (fat, protein and lactose) and some minerals (calcium, phosphorus and magnesium) were greater in colostrum than in milk. The regression of daily and monthly milk yield on lactoferrin concentration in colostrum was positive and highly significant (P<0.01), while the regression of these characters on lactoferrin concentration in colostrum was positive and significant (P<0.05). Result revealed that the regression of minerals (calcium and magnesium) on lactoferrin in colostrum was positive and highly significant (P<0.01). Moreover, the regression of phosphorus and iron in colostrum was negative and significant (P<0.05). The regression relationship of amino acids (essential and non-essential) on lactoferrin in colostrum was varied between positive and negative and some of them was significant. In conclusion, it is possible to predict the milk yield and its constituents of Holstein cows through lactoferrin concentrations either in milk of colostrum for selection purposes.